Mindful Marijuana Smoking: Health Tips for Cannabis Smokers - Braunstein, Mark Mathew (Rowman & Littlefield Publishers, 2022)
Learn how to smoke cannabis in a way that reduces the health risks of smoking. As an herbal remedy, cannabis can lift your mood and can treat a long list of ailments. But the way that most of us take a hit of pot needlessly takes a hit on our health. It is high time for health-conscious cannabis consumers to learn a new way of smoking that reduces its risks. In Mindful Marijuana Smoking, Mark Mathew Braunstein offers sound advice on every phase of the cannabis smoking experience, presenting health tips based on solid science. Whether with rolling papers, hand pipes, waterpipes, or herbal vaporizers, each method of cannabinoid delivery has both risks and rewards. Chapters are devoted to each method so that you can learn how to maximize their benefits and reduce their hazards, as well as how to protect your health even before you take a puff. And once you’ve inhaled the smoke, this book assures you that you don’t need to hold your breath to reap all the benefits of cannabis. Additionally, this book teaches readers how to assure an herb’s purity, as both black market and corporate cannabis keep dirty secrets about how they were grown, and readers will learn about the potential impurities in rolling papers and vaping oils. The stronger the dose, the less you need to toke, so you’ll find instructions on how to properly store cannabis to retain its potency. Finally, after you’ve smoked, you’ll find guidance on why and how to relieve your parched mouth and to replenish nutrients that are depleted by smoking. Potheads and patients, tenderfoot tokers and seasoned stoners, dabbling dilettantes and cannabis connoisseurs, all need to read this book. By following its many health tips, when you light up, you can lighten up.